Researchers and Students in the field of Arts and Humanities in Croatia - Aparac, Tatjana; Vrana, Radovan (1999)
Since there hasn't been any systematic approach to the investigation of user's behaviour in the changed information environment in Croatia, a strong need was felt for undertaking a number of investigations about the issue of seeking and getting teaching and research information in the field of Arts and Humanities. The authors felt that a systematically designed and organised research study would produce important information about students and researchers' attitudes, needs and demands both for printed materials and for materials available on the global network. One of the authors' presuppositions was that Croatian university teachers and researchers in Arts and Humanities are enormously dependant on paper sources and domestic literature. Although there was some evidence that the new generation of university teachers and researchers has been using new information technology (IT) more frequently, documented data about this were still missing. The other hypothesis was related to students' attitudes towards new teaching methods and techniques - which has often been provoked by their own interest rather than by a systematic approach at the appropriate department, faculty or university. Therefore, it was expected that the results of the survey would cast more light on the design and conduct of programs for user education in the network environment. The first phase of the research was designed to serve as a pilot study comprising data relevant to the student population at the Faculty of Philosophy at the University of Zagreb.
Projekt MZOS
ENG